Linkage to primary-care public health facilities for cardiovascular disease prevention: a community-based cohort study from urban slums in India. Issue 8 (6th August 2021) - Pakhare, Abhijit; Joshi, Ankur; Anwar, Rasha; Dubey, Khushbu; Kumar, Sanjeev; Atal, Shubham; Tiwari, Ishan Raj; Mayank, Vipul; Shrivastava, Neelesh; Joshi, Rajnish
Abstract : Objectives: Hypertension and diabetes mellitus are important risk factors for cardiovascular diseases (CVDs). Once identified with these conditions, individuals need to be linked to primary healthcare system for initiation of lifestyle modifications, pharmacotherapy and maintenance of therapies to achieve optimal blood pressure and glycaemic control. In the current study, we evaluated predictors and barriers for non-linkage to primary-care public health facilities for CVD risk reduction. Methods: We conducted a community-based longitudinal study in 16 urban slum clusters in central India. Community health workers (CHWs) in each urban slum cluster screened all adults, aged 30 years or more for hypertension and diabetes, and those positively screened were sought to be linked to urban primary health centres (UPHCs). We performed univariate and multivariate analysis to identify independent predictors for non-linkage to primary-care providers. We conducted in-depth assessment in 10% of all positively screened, to identify key barriers that potentially prevented linkages to primary-care facilities. Results: Of 6174 individuals screened, 1451 (23.5%; 95% CI 22.5 to 24.6) were identified as high risk and required linkage to primary-care facilities. Out of these, 544 (37.5%) were linked to public primary-care facilities and 259 (17.8%) to private providers. Of the remaining, 506 (34.9%) did not get linked to any provider and 142 (9.8%) defaulted after initial linkages (treatment interrupters). On multivariate analysis, as compared with those linked to public primary-care facilities, those who were not linked had age less than 45 years (OR 2.2 (95% CI 1.3 to 3.5)), were in lowest wealth quintile (OR 1.8 (95% CI 1.1 to 2.9), resided beyond a kilometre from UPHC (OR 1.7 (95% CI 1.2 to 2.4) and were engaged late by CHWs (OR 2.6 (95% CI 1.8 to 3.7)). Despite having comparable knowledge level, denial about their risk status and lack of family support were key barriers in this group. Conclusions: This study demonstrates feasibility of CHW-based strategy in promoting linkages to primary-care facilities.